Edukasi Konsumsi Tablet Fe dan Susu Kedelai untuk pencegahan Anemia pada Ibu Hamil di Bidan Praktek Mandiri Muzilatulnisma Kota Jambi - Sirly Patriani; Selpyani Sinulingga; Suci Rahmani Nurita (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Anemia is the biggest public health problem in the world, especially in the group of pregnant women. The prevalence of anemia in pregnant women worldwide is 41.8%, the prevalence of anemia in pregnant women in developed countries is 18%, while the average prevalence of anemia in pregnant women in developing countries is around 63.5% - 80%. the results of basic health research (Riskesdas) in 2013 the prevalence of pregnant women with anemia in Indonesia was 37.1%. cases of anemia in pregnant women is due to iron deficiency. The risk of pregnant women who experience anemia face the risk of death in pregnancy. Every year there are 500 thousand postnatal maternal deaths worldwide, as much as 20-40% of the main causes of death are anemia. BPM muzilatulnisma is a clinic that serves maternal and child health in the city of Jambi which has been standardized as a Delima midwife and as a certified mom and baby treatment clinic. Consumption of Fe tablets and soy milk is one way to prevent anemia in pregnant women. This community service is carried out by providing education through counseling for pregnant women about anemia prevention. held from March to August 2022 at the Muzilatulnisma Independent Practice Midwife, Jambi City. The purpose of this service activity is to provide education by providing health education/counseling on how to prevent anemia in pregnant women. With the hope of increasing the knowledge and awareness of pregnant women in consuming Fe tablets and soy milk in the prevention of anemia. The results obtained after community service was carried out were an increase in knowledge of pregnant women about anemia prevention at BPM Muzilatulnisma Jambi City. The implementation of community service activities carried out by providing education (counseling) using leaflets was able to increase the knowledge of pregnant women about anemia prevention.